(untitled) (Research, Society and Development, 2020)
Objective: to carry out an analysis of the consequences for mental health arising from the period of social isolation during the COVID-19 pandemic and to foreshadow coping strategies to minimize them. Methodology: this is an integrative literature review, carried out based on the search for scientific publications indexed in the databases: MEDLINE via PubMed, Europe PMC, Lilacs and SciELO. The following descriptors were used: COVID-19, social isolation, pandemics and mental health. At the end of the searches, 49 publications met the eligibility criteria and were selected to compose the study. Results: in view of the findings extracted from the selected studies, it was noticed that individuals subjected to social isolation are more susceptible to presenting mental health disorders, due to deprivation and social restraint, with symptoms of psychological distress, especially related to stress, anxiety and depression. Conclusion: this study allowed us to reflect on the need to ensure clear and informative communication on strategies to reduce these symptoms of psychological distress, in addition to providing fundamental psychological and social support for these vulnerable individuals.